A Statistical Study of Spatial Variation of Relativistic Electron Precipitation Energy Spectra With Polar Operational Environmental Satellites. Issue 5 (2nd May 2018) - Shekhar, S.; Millan, R. M.; Hudson, M. K.
Abstract: The mechanisms that drive relativistic electron precipitation (REP) from the radiation belts can be better understood with a better knowledge of the particle energies involved. National Oceanic and Atmospheric Administration Polar Operational Environmental Satellites, being a network of multiple satellites, can provide multiple point spectral data over a long time period, including the Van Allen Probe's era. The number of energy channels is limited, but the particle detectors on Polar Operational Environmental Satellites have a narrow field of view allowing an investigation of bounce loss cone particles. We use the ratio of count rates in the E 3 (>300 keV) and the P 6 (>700 keV) channels as a parameter to define spectral hardness. Using this parameter, the spatial variation of spectral hardness of REP events was investigated. It was found that very soft events were mostly found in the dusk‐midnight‐early morning magnetic local time sectors and L ∼ 5–7 while the hardest events were located in the postnoon sector peaking at L ∼ 4–5. The hardest events peaked at lower L shells, and less than 20% were coincident with low‐energy (30–80 keV) proton precipitation. Further, around 70% of nightside REP coincident with proton precipitation was associated with stretched magnetic field lines indicating that curvature scattering may have been an important driver. Around 62% of nightside REP coincident with proton precipitation associated with relaxed magnetic field lines, suggesting a mechanism other than magnetic field curvature scattering, was highly energetic. Key Points: Hardest relativistic electron precipitation events were found to be more probable in the 6 to 19‐hr magnetic local time sector and at lower L shells (L 4.6) About 70% of nightside events accompanied by 30–80 keV proton precipitation14 were associated with magnetic field tail stretching Sixty‐two percent of nightside events accompanied by 30–80 keV proton precipitation associated with relaxed magnetic field lines were highly energetic